Parliament as a "Window of Opportunities": A Study on the Pursuit of Business Interests by Entrepreneurs with Mandates - СакаеваМария Маратовна (Journal of Economic Sociology, 2012)
The article is devoted to the election of businessmen into regional legislatures. Transition from business to politics without withdrawing the entrepreneurial activity is considered as a rationalized behavior of economic actors. The author supposes that mandate of a legislator serves as an effective tool for pursuing business interests. Legislature Assembly of Saint-Petersburg is a case for studying opportunities and resources which are available to business people becoming its memebers. The study demonstrates the barriers faced by entrepreneurs pursuing their interests through accumulation of political, administrative, and other resources. The author focuses on the scale of the business people elections to regional legislatures of North-Western Federal Okrug. The research findings show that a new political status presents a «window of opportunities», widening entrepreneurs capacities to optimize their market positions. At the same time, limitations of these opportunities are examined.